PENGARUH ONSET LAKTASI TERHADAP PRAKTIK PEMBERIAN ASI PADA NEONATUS DI KOTA PALANGKA RAYA - , Erina Eka Hastini ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Compared to the national target in which the coverage is determined to be 80%, exclusive breastfeeding has only met 32% which is far from the target. In 2008, the coverage of exclusive breastfeeding in Palangkaraya Municipality was 9.84% which was considered very low and in 2009, however, the coverage only 12.82% with no number early initiation of breastfeeding found. Studies have shown that lactation onset plays important roles in pre-lacteal feeding or formula milk feeding. By being known the effect onset of lactation on breastfeeding practice, it is expected that this can improve breastfeeding among neonates fully in Palangkaraya Municipality. Objective: The known effect onset of lactation on breastfeeding among neonates in Palangkaraya Municipality, Central Kalimantan Province. Method: The design was prospective cohort with a sample size of 106 mothers who had a baby aged 0-1 month. The independent variable was lactation onset, the dependent variable was breastfeeding and the extraneous variables were parity, childbirth method, and maternal overweight as well as early initiation of breastfeeding. Data analysis used univariable analysis with frequency and percentage distribution, bivariable analysis with chi-square test, and multivariable analysis with logistic regression using Stata Version 11.1. Result: The multivariable result with modeling showed a significant relationship between onset of lactation and breastfeeding in neonates (RR=1,9